2023
DOI: 10.1039/d3cc02205f
|View full text |Cite
|
Sign up to set email alerts
|

Precision nanoengineering for functional self-assemblies across length scales

Nonappa

Abstract: As nanotechnology continues to push the boundaries across disciplines, there is an increasing need for engineering nanomaterials with atomic-level precision for self-assembly across length scales, i.e., from the nanoscale to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 239 publications
0
4
0
Order By: Relevance
“…Ligand-protected metal nanoclusters make excellent building blocks to create self-assembled hierarchical frameworks. 192,276,277 An interesting phenomenon of self-assembly arises in Te NWs when the surface is modified with Ag 44 ( p -MBA) 30 nanocluster. The p -MBA ligand shells initiate a H-bonding interaction among themselves, leading to the formation of a bilayer assembly of NWs oriented at an angle of 81° w.r.t.…”
Section: Chemical Reactivity Of Ligand-protected Atomically Precise M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ligand-protected metal nanoclusters make excellent building blocks to create self-assembled hierarchical frameworks. 192,276,277 An interesting phenomenon of self-assembly arises in Te NWs when the surface is modified with Ag 44 ( p -MBA) 30 nanocluster. The p -MBA ligand shells initiate a H-bonding interaction among themselves, leading to the formation of a bilayer assembly of NWs oriented at an angle of 81° w.r.t.…”
Section: Chemical Reactivity Of Ligand-protected Atomically Precise M...mentioning
confidence: 99%
“…280 The patchy distribution of ligands around the metal core facilitates symmetry breaking and eventually directs a preferential interlayer H-bonding between the carboxylic acid groups of the p -MBA ligands. 276,277,279 Chakraborty et al showed hydrogen bonding-induced chemical interaction between the Ag 44 ( p -MBA) 30 nanocluster and a plasmonic gold nanorod (GNR), leading to the encapsulation of the latter (Fig. 14B), here denoted as GNR@Ag 44 .…”
Section: Chemical Reactivity Of Ligand-protected Atomically Precise M...mentioning
confidence: 99%
“…In addition, these nanoparticles are capable of increasing the antenna's gain and efficiency, while also preserving its lightweight and flexible nature. For example, in high-precision positioning systems, metal nanoparticles demonstrate particularly effective performance [22].…”
Section: Introductionmentioning
confidence: 99%
“…The thiolate monolayer protecting the NC surface is dynamic in nature, , and the metal–ligand interface controls the atom transfer in an intercluster reaction . However, most examples of interparticle interactions are purely driven by supramolecular interactions, such as hydrogen-bonding, van der Waals, C–H···π, π···π, and electrostatic interactions where the reacting particles retain their intrinsic properties in the superstructures. , We recently reported the formation of a self-assembled 2D superlattice of monodispersed Ag–Au–alloy NPs by reacting polydispersed Ag NPs with [Au 25 (SR) 18 ] − NC . As studied using mass spectrometry, the reaction mechanism suggested an interparticle atomic exchange (metal–ligand species), and the metal–ligand interface was crucial for the reaction .…”
Section: Introductionmentioning
confidence: 99%